Global political economy and the wealth of nations : performance, institutions, problems, and policies - O'Hara, Phillip Anthony, 1954- (Routledge frontiers of political economy, 2004)
This comprehensive collection documents the major processes, performance, institutions, problems and policies associated with global political economy.